Evaluation of dogs (Canis familiaris) as an indicator of Japanese encephalitis (JE) outbreaks: A retrospective serological study in the Seoul metropolitan area around the 2010 resurgence of JE in the Republic of Korea - Jung-Yong Yeh (One Health, 2022)
Japanese encephalitis (JE) is a mosquito-borne zoonotic neurological disease caused by Japanese encephalitis virus (JEV). JEV is the most common cause of viral encephalitis in Southeast Asia and the Western Pacific Rim. The fatality rate due to JE can reach 25% and up to 50% of the patients who survive develop permanent neurological damage. The annual incidence of human JE markedly increased in the Republic of Korea (ROK) in 2010 but the reason for the reemergence of JE in the ROK has not been established. This study aimed to assess the extent of exposure of domestic dogs to JEV in the Seoul metropolitan area, one of the most populated areas in the world. This cross-sectional study serologically investigated the spread of JEV in the dog population. Using serum neutralization test, we examined 3597 serum samples collected from pet, shelter, stray, and farmed dogs in the Seoul metropolitan area from 2006 to 2012. JEV-neutralizing antibodies found in shelter, stray, and farmed dogs sampled in approximately 2010 demonstrated increased JEV circulation in the dog population during the 2010 resurgence of JE reported among humans in the ROK. Five out of 1102 pet dogs (0.5%) were found to be neutralizing antibodies against JEV and 24 of 719 shelter dogs (3.1%) were positive with a peak of 13.0% in 2010. In addition, 25 of 690 stray dogs (3.6%) were positive with a peak of 9.7% in 2009, a year before the 2010 resurgence of JE. Furthermore, 39 of 1086 farmed dogs (3.6%) were seropositive with a peak of 9.2% in 2009. We therefore suggest that monitoring dog populations for seroconversion or seropositive dogs within JEV-active endemic areas may be useful for identifying risk areas for JE outbreaks and that JEV activity in dogs can be an indicator as the harbingers of JEV in humans.